COLLABORATIVE STRATEGY ON SUPPORTING BILINGUALISM EDUCATION IN ONLINE LEARNING - Mariati, Sri; Wiriawan, I Ketut (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Being bilingual is a common phenomenon around the world. Since many children learn two different languages from an early age, bilingual programs get more attention in the educational field. The programs drive the development of instructional strategies to cope with the goals of the bilingual education programs and to promote children’s competencies in two languages. In promoting the degree of bilingualism in the classroom, the challenge is not only to do with the choice of appropriate strategies but also to deal with children motivation to learn. The lack of motivation on the part of the students may cause some kind of resistance in term of the instructional process even though the teachers have employed carefully selected strategies for teaching strategies. The challenge is even more when the instruction should be conducted in online learning mode. To cope with this problem, the collaborative strategy is proposed as the possible solution. The purpose of the study was to explore the implementation of the collaborative strategy between teachers & parents, and how the role of technology become important in teaching and learning bilingual students. This study was conducted by the library research method. In this study, the researcher reviewed some articles and draw the result descriptively from the secondary data. The finding of the study showed collaborative strategy can help the students and teachers in bilingual education by considering teacher & parent partnerships and technology readiness. For the implementation of collaborative strategy in online learning, some technology cannot be used effectively like chatting in online discussion. Then, parents as tutors at home need to fulfil standard requirements before conducting teacher-parent partnerships.